The amazing 1960’s: a tale of counterculture’s impact on Spider-Man - Costa, Ismael Soares (My University, 2020)
This research intends to investigate if Spider-Man's comic books made him representative of Counterculture in the 1960's. The object of analysis is contextualized in the decade that it was created, the social circumstances present in American society during that time are presented, and finally an analysis is done on the repercutions of both Spider-Man's comic books and Counterculture on each other and on society as a whole. The method used is a bibliographical research, with studies on the hero's journey, on social imaginary and cultural studies about the development of technocracy and on the role of comic books as social commentary. Our main references are Bronislaw Baczko, on social imaginary; Joseph Campbell, on the hero's journey; and Theodore Roszak, on Counterculture. The conclusion indicates that Spider-Man comics, in fact, did represent values of Counterculture. [resumo fornecido pelo autor]
Essa pesquisa tem a intenção de investigar se histórias em quadrinhos do Homem-Aranha fizeram dele representativo da Countracultura nos anos 60. O objeto de análise contextualizado na década que foi criado, as circunstâncias sociais presentes na sociedade Americana durante essa época apresentados e finalmente uma análise nas repercurssões que ambos - o Homem-Aranha e a Contracultura - tiveram um no outro e na sociedade como um todo. O método usado é uma pesquisa bibliográfica, com estudos sobre a jornada do herói, estudos sobre o desenvolvimento da tecnocracia e no papel de histórias em quadrinho como comentário social. Nossas referências principais foram Bronislaw Baczko, sobre o social imaginário; Joseph Campbell sobre a jornada do herói; e Theodore Roszak, sobre a Contracultura. A conclusão indica que histórias em quadrinho do Homem-Aranha, de fato, representavam valores da Contracultura. [resumo fornecido pelo autor]
Keywords: Literatura; Histórias em quadrinhos; Homem-Aranha (Personagem fictício); Heróis; Contracultura